2009
DOI: 10.1111/j.1476-5381.2009.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA mismatch repair (MMR)‐dependent 5‐fluorouracil cytotoxicity and the potential for new therapeutic targets

Abstract: The metabolism and efficacy of 5-fluorouracil (FUra) and other fluorinated pyrimidine (FP) derivatives have been intensively investigated for over fifty years. FUra and its antimetabolites can be incorporated at RNA-and DNA-levels, with RNA level incorporation provoking toxic responses in human normal tissue, and DNA-level antimetabolite formation and incorporation believed primarily responsible for tumour-selective responses. Attempts to direct FUra into DNA-level antimetabolites, based on mechanism-of-action… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 120 publications
2
55
0
1
Order By: Relevance
“…Various preclinical data suggested that the effect of 5-FU chemotherapy was dependent on the MMR status (29,30). Several studies have shown that 5-FU induces G 2 arrest less efficiently in MMR-deficient cells than in their MMR-proficient counterparts (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Various preclinical data suggested that the effect of 5-FU chemotherapy was dependent on the MMR status (29,30). Several studies have shown that 5-FU induces G 2 arrest less efficiently in MMR-deficient cells than in their MMR-proficient counterparts (31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…Defective DNA MMR might be one mechanism for tumor resistance to 5-FU and a reason that MMR deficient colon cancer cells are not readily killed by 5-FU. [12][13][14][15] However, in vitro studies and clinical data do not accord well together. Some authors found that fluorouracil-based adjuvant chemotherapy benefited patients with stage II or stage III colon cancer with MSS and MSI-L phenotype but not those with tumors exhibiting MSI-H. 2,3 They suggested that adjuvant 5-FU-based chemotherapy may not be useful in stage II and III MMR deficient colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A similar finding was reported by Adamsen et al (34) who suggested that BER (or NER) is sufficient to repair the bolus-5FU-induced DNA damage (FdUTP/dUTP mis-incorporation) in the absence of functional MMR in the TP53-proficient HCT116 cell line. In addition, Li et al (35) have shown that MMR-deficient cells incorporate higher levels of fluoropyrimidine metabolites than MMR-proficient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Differences between the four cell lines in the conversion of 5FU to its active metabolites and/or its catabolism by dihydropyrimidine dehydrogenase to inactive metabolites is another possible explanation for the different number of 5FU-induced DSBs in the four cell lines at the same drug concentration [reviewed by Koopman et al (27) and Li et al (35)]. …”
Section: Discussionmentioning
confidence: 99%